EKSPLORASI PERAN METAVERSE DALAM INOVASI LAYANAN KEUANGAN: PELUANG, TANTANGAN, DAN MASA DEPAN PERBANKAN DIGITAL - Wahyudin, Ahmad; Faisol, Faisol; Haryadi, Bambang; Hayati, Nur (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
The rapid advancement of digital technology has led to the emergence of the Metaverse as a potential innovation in the financial sector, particularly in digital banking services. This study explores the role of the Metaverse in financial service innovation by analyzing its opportunities, challenges, and future implications for digital banking. The findings indicate that Metaverse-based financial services offer immersive interactions, enhanced customer experience, and the development of new financial products such as blockchain-based transactions and digital asset investments. However, challenges such as regulatory uncertainties, cybersecurity risks, technological infrastructure limitations, and customer adoption barriers must be addressed for successful implementation. The study concludes that while the Metaverse has the potential to revolutionize financial services, effective strategic planning, investment in technology, regulatory frameworks, and public digital literacy enhancement are essential for its sustainable integration into the banking industry.